IMPLEMENTASI BIMBINGAN KELOMPOK TERHADAP SELF CONFIDENCE KORBAN BODY SHAMING - Naser, Muhammad Nikman; Sari, Kurnia; Yuhaswita, Yuhaswita (Jurnal Bimbingan dan Konseling Borneo, 2024)
The problem in this study is the rampant phenomenon of body shaming in MAN Bengkulu Selatan students. The purpose of this study was to describe the implementation of group guidance on the self confidence of victims of body shaming in MAN Bengkulu Selatan students. This research is a descriptive qualitative research using the case study method. Data collection techniques in this study by conducting observations, interviews, and documentation. The results of this study indicate that students who are victims of body shaming tend to have low self-confidence where this can be seen from the physical appearance factor. After students who were victims of body shaming participated in group guidance, the students were able to increase their self-confidence again. This shows that group guidance services for self confidence of body shaming victims of MAN Bengkulu Selatan students are successful and have a positive impact on changes in the behavior of students who are victims of body shaming.Â Permasalahan dalam penelitian ini adalah maraknya fenomena body shaming pada siswa MAN Bengkulu Selatan. Tujuan penelitian ini adalah untuk mendeskripsikan implementasi bimbingan kelompok terhadap self confidence korban body shaming pada siswa MAN Bengkulu Selatan. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan metode studi kasus. Teknik pengumpulan data dalam penelitian ini dengan melakukan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukan bahwa siswa yang menjadi korban body shaming cenderung memiliki self confidence yang rendah dimana hal ini dapat dilihat dari faktor penampilan fisik. Setelah siswa korban body shaming mengikuti bimbingan kelompok, para siswa mampu untuk meningkatkan kembali kepercayaan diri mereka. Hal ini menunjukan bahwa layanan bimbingan kelompok terhadap self confidence korban body shaming siswa MAN Bengkulu Selatan berhasil dan memberikan dampak positif terhadap perubahan perilaku siswa korban body shaming.